Intercultural dialogue and teacher training in the ANPED (2002-2015): is inclusion or exclusion? - Souza, Sawana Araújo Lopes de (Universidade Estadual Paulista, Faculdade de Ciências e Letras de Araraquara, 2017)
This article comes from a mapping carried out in the Working Group (WG) 8 of the National Association of Postgraduate and Research in Education (ANPEd) that deals with teacher education. The objective of this study is to investigate the academic production of articles that were approved in the aforementioned academic event between the years 2002 and 2015 and their correlation with the field of teacher education. This academic production is analyzed on the basis of Freire (1996), Gatti (2011), who deal with teacher training and, for intercultural dialogue, we base ourselves on Latin American authors such as Candau & Russo (2010), Walsh (2007,2009 ), Santos (2010). In addition, methodologically, it is characterized by being of the qualitative and documentary type. For analysis of the data we adopted as a technique the content analysis of Bardin (2011). We conclude that teacher training, both initial and continuing, must have a debate on interculturality, since there is interaction between cultures in both school and university settings. Furthermore, based on this mapping, we find that this debate still has little representation in ANPEd (2002-2015), that is, 1% of scientific research.